Physicochemical compatibility and emulsion stability of propofol with commonly used analgesics and sedatives in an intensive care unit. Issue 5 (29th September 2016) - Gersonde, Franziska; Eisend, Swantje; Haake, Nils; Kunze, Thomas
Abstract : Objectives: The purpose of this study was the determination of the physicochemical compatibility and emulsion stability of propofol with other sedatives and analgesics (clonidine hydrochloride, dexmedetomidine, 4-hydroxybutyric acid, ( S )-ketamine, lormetazepam, midazolam hydrochloride, piritramide, remifentanil hydrochloride and sufentanil citrate) that are frequently administered together intravenously. Methods: Drugs were mixed with propofol and stored without light protection at room temperature. Samples were taken at 10 points of time over 7 days. The physical stability and emulsion stability in particular were analysed by visual and microscopical inspection and by measurement of the pH value, zeta potential and globule size distribution. In addition, high-performance liquid chromatography and mass spectrometry were used to identify chemical incompatibilities. Results: 4-Hydroxybutyric acid, midazolam hydrochloride, piritramide and remifentanil hydrochloride are physically incompatible when mixed with propofol. The reason for this is the development of an increased fraction of oil droplets >5 µm leading to a higher risk of emboli. Moreover, propofol is chemically incompatible with remifentanil. The sorption of propofol to the rubber stopper of the syringe was another detectable incompatibility. Conclusions: Propofol should not be administered with 4-hydroxybutyric acid, remifentanil hydrochloride, midazolam hydrochloride and piritramide through the same intravenous line. Based on the risk of sorption to the rubber material, propofol should be used with caution. A drug loss might occur that leads to an underdosing of the patient requiring a dose adjustment to avoid any adverse consequences. As a result of this study, the drug safety in intensive care units could be optimised.